2017
DOI: 10.3390/magnetochemistry3010014
|View full text |Cite
|
Sign up to set email alerts
|

Charge Ordering Transitions of the New Organic Conductors δm- and δo-(BEDT-TTF)2TaF6

Abstract: Structural, transport, and magnetic properties of new organic conductors composed of (BEDT-TTF) 2 TaF 6 , where BEDT-TTF is bis(ethylenedithio)tetrathiafulvalene, have been investigated. Two δ-type polymorphs, monoclinic and orthorhombic phases are obtained by the electrocrystallization. Both phases show a semiconductor-insulator phase transition at 276 K and 300 K for the monoclinic and orthorhombic phases, respectively; the ground state of both salts is a nonmagnetic insulating state. The low-temperature X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Furthermore, as explained in the Introduction, no mixed BEDT-TTF/XF 6 salts are known to date and the pure forms showed a variation of packing type and conducting properties, while keeping a 2:1 donor:anion stoichiometry. However, an inspection of the reported BEDT-TTF/XF 6 (X = P, Ta) salts indicated that the orthorhombic phases β-(BEDT-TTF) 2 PF 6 [29] and δ o -(BEDT-TTF) 2 TaF 6 [33] were isostructural; therefore, an orthorhombic phase with a mixed anion composition could be expected to occur. Beside the use of XF 6 -(X = Ta, P) anionic alloys, we also envisaged the addition of equimolar TaF 6 -/TaF 5 mixtures in the electrocrystallization cell, assuming that condensation might take place to provide [Ta 2 F 11 ]in situ.…”
Section: Radical Cation Salts Of Bedt-ttfmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, as explained in the Introduction, no mixed BEDT-TTF/XF 6 salts are known to date and the pure forms showed a variation of packing type and conducting properties, while keeping a 2:1 donor:anion stoichiometry. However, an inspection of the reported BEDT-TTF/XF 6 (X = P, Ta) salts indicated that the orthorhombic phases β-(BEDT-TTF) 2 PF 6 [29] and δ o -(BEDT-TTF) 2 TaF 6 [33] were isostructural; therefore, an orthorhombic phase with a mixed anion composition could be expected to occur. Beside the use of XF 6 -(X = Ta, P) anionic alloys, we also envisaged the addition of equimolar TaF 6 -/TaF 5 mixtures in the electrocrystallization cell, assuming that condensation might take place to provide [Ta 2 F 11 ]in situ.…”
Section: Radical Cation Salts Of Bedt-ttfmentioning
confidence: 99%
“…When the electrocrystallization experiment was performed with pure (n-Bu 4 N)TaF 6 , the already known orthorhombic δ o -phase (BEDT-TTF) 2 TaF 6 [33], reminiscent of the orthorhombic β-(BEDT-TTF) 2 PF 6 phase [29], was obtained as black needles together with black platelets of (BEDT-TTF) 3 Ta 2 F 10 O as a side product. Curiously, the use of a nominal mixture Ta/P 0.2/0.8 provided needle-like crystals (Figure S13) of the same orthorhombic δ o -phase in the group Pnna, formulated as δ o -(BEDT-TTF) 2 (TaF 6 ) 0.43 (PF 6 ) 0.57 , with one independent donor and half an anion in the asymmetric unit (Figure 4).…”
Section: Radical Cation Salts Of Bedt-ttfmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Interestingly, while Bechgaard and Fabre salts are isostructural, 5,13,16 2 : 1 mixed valence salts of bis(ethylenedithio)-tetrathiafulvalene (BEDT-TTF), another agship donor in the eld of organic conductors and superconductors, 2,17,18 with octahedral monoanions XF 6 À show, in comparison, a rich collection of structures and, consequently, physical properties. Indeed, triclinic and orthorhombic phases have been described for a-(BEDT-TTF) 2 -PF 6 19 and b-(BEDT-TTF) 2 PF 6 , 20 respectively, monoclinic 21 and orthorhombic 22 structures for b-(BEDT-TTF) 2 AsF 6 , a monoclinic phase for b-(BEDT-TTF) 2 SbF 6 , 23 isostructural to the AsF 6 À counterpart, and, nally, monoclinic and orthorhombic structures for d-(BEDT-TTF) 2 TaF 6 , 24 together with a monoclinic k-(BEDT-TTF) 2 TaF 6 phase. 25 In the course of our own investigations on chiral conductors, 26,27 culminating with the rst experimental observation of the electrical magnetochiral anisotropy effect (eMChA), 28 we observed as well a strong dependence of the donor packing on the anion size in the (DM-EDT-TTF) 2 XF 6 series (DM-EDT-TTF ¼ dimethyl-ethylenedithio-TTF, Scheme 1, X ¼ P, As, Sb).…”
Section: Introductionmentioning
confidence: 99%
“…BEDT-TTF charge transfer salts are characterized by a very large structural diversity associated with different electrical and magnetic properties. Tadashi Kawamoto et al, in their contribution to this issue [10], describe structural, transport, and magnetic properties two δ-type polymorphs of the salt (BEDT-TTF) 2 TaF 6 with Charge Ordering transitions.…”
mentioning
confidence: 99%